Decision support system for selecting the best midwife by applying the exponential comparison method Exponential comparison method (mpe) case study puskesmas bandar kota pagar alam - Afrizal, Nanda; Suranti, Dewi; Fredricka, Jhoanne (Jurnal Komputer Indonesia, 2023)
In the current era of digital and globalization, the need for fast, precise and accurate information is very important. To improve the quality of midwives' performance, at Bandar Health Center, Pagaralam City, periodic performance assessments will be needed to motivate the midwives to be more enthusiastic in increasing their performance dedication. However, it is not an easy matter to make a selection to determine the best midwife. Decision support systems (DSS) can provide information and help provide various alternatives that can be used in the decision making process. The existence of a decision support system will also have a positive impact on the sustainability of midwives' performance based on regulations and assessment results. It will be used as material for decision making that can be taken according to expected needs. The results of this process are in the form of a midwife assessment stage as a recommendation in making decision to select a midwife who is suitable for receiving an award as the best midwife. This application was created using the Visual Basic Net programming language and SQL Server/database.